1992
DOI: 10.1063/1.1142926
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different Langmuir probe surface cleaning procedures on its I-V characteristics

Abstract: An influence of different procedures and conditions of cleaning the Langmuir probe surface on its current-voltage characteristic in a plasma is experimentally studied. It is shown that the electronic bombardment of the probe surface and its ohmic warm-up lead to a very effective cleaning of the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The meaning of temperature-dependent contaminations of Langmuir probes is shown in figure 1, and it is discussed in general by Motley [4] and by Wehner and Medicur [5]. Some related experimental work has been performed, for example by Buzzi et al [6] on a cesium plasma, by Shun'Ko [7] who tested different methods of probe cleaning and by Amatucci et al [8] operating an indirectly heated probe. In the present paper, the contamination of Langmuir probes is studied in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…The meaning of temperature-dependent contaminations of Langmuir probes is shown in figure 1, and it is discussed in general by Motley [4] and by Wehner and Medicur [5]. Some related experimental work has been performed, for example by Buzzi et al [6] on a cesium plasma, by Shun'Ko [7] who tested different methods of probe cleaning and by Amatucci et al [8] operating an indirectly heated probe. In the present paper, the contamination of Langmuir probes is studied in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…We can suppose here that precise probe measurements in SF 6 ion-ion plasma require chemically non-active materials for the electrodes like Pt and probably Au and that periodical cleaning of the probe surface with negative potential is necessary, since asymmetry in the positive and negative ion-assisted deposition was observed for all tested materials (copper, tungsten, and Pt-Ir alloy). Moreover, one should also keep in mind that applying a positive potential to the probe which is sometimes used for probe cleaning 20,21 can result in intense film deposition process in the ion-ion SF 6 plasma.…”
Section: B Film Deposition On Langmuir Probe Tips Of W and Ptmentioning
confidence: 99%
“…4 By polarizing the probe negatively or positively to a large potential, ion or electron bombardment can remove the contamination layer. 5,6 This method is efficient however, only if the time scale for recontamination is large compared with the time needed to acquire the probe characteristic. In the case of plasma containing hydrocarbon ions, which we have used for dissociative recombination measurements, we observed that this condition is not always respected.…”
Section: Introductionmentioning
confidence: 99%